Cellular census of human fibrosis defines functionally distinct stromal cell types and states - Thomas B. Layton (Nature Portfolio, 2020)
New anti-fibrotics aided by a better understanding of fibrotic cell subsets and their functions are needed. Here the authors perform single-cell RNA-seq and CyTOF on nodules from patients with Dupuytren’s disease to map subsets and the state of mesenchymal cells during pathogenic fibrogenesis.